Manejo de bacias hidrográficas e sua influência sobre os recursos hídricos - Aparecido, Camila Fernandes Ferreira; Vanzela, Luiz Sergio; Vazquez, Gisele Herbst; Lima, Ronaldo Cintra [UNESP] (My University, 2016)
Studies on the use and occupation of soil explored by various segments of urban, rural and industrial societies, associated to the watershed characteristics are extremely important for water resources management and sustainability. Therefore, this work aimed to evaluate the influence of different managements of soil use and occupation associated to declivity and superficial flow water resources of watersheds located in Triângulo Mineiro – MG. The study was conducted by monitoring the flow and sediment in 4 basins from September 2013 to October 2014, besides the determination of soil use and occupation, declivity and superficial flow during this time. The obtained mathematical models showed that the ratio of the different soil uses and occupations interferes with the specific production and sediment concentration and the specific flow of watersheds as well, while the amount of superficial flow interferes with the specific sediment production. The simulations results of the management of watersheds’ use and occupation showed that the conservation of native forests, the conservationist techniques of soil use and the minimization techniques of diffuse transport from urban areas are essential for keeping water availability and quality.
Watershed management and its influence on the hydric resources
Keywords: Land use; Runoff; Slope